SOCIAL RESPONBILITY BANK SYARIAH DENGAN PENDEKATAN ISLAMIC SOCIAL REPORT DAN PENGARUHNYA TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN - Marheni Marheni (Budgeting: Jurnal Akuntansi Syariah, 2020)
Responsibility disclosure and islamicity performance index on the profitability of sharia banks in the period 2015-2019, The samples used are Bank Muamalat, Bank Mandiri Syariah Bank, Mega Syariah, BRI syariah, BCA syariah and BNI syariah period 2015-2019, Analytical technique used in this research with multiple linear regression analysis. he result of analysis shows that Corporate Social Responsibility has no significant effect on profitability of syariah bank and on Islamicity Performance Index has significant influence on profitability of syariah bank